(5w+4)(7+w)=0

Simple and best practice solution for (5w+4)(7+w)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5w+4)(7+w)=0 equation:


Simplifying
(5w + 4)(7 + w) = 0

Reorder the terms:
(4 + 5w)(7 + w) = 0

Multiply (4 + 5w) * (7 + w)
(4(7 + w) + 5w * (7 + w)) = 0
((7 * 4 + w * 4) + 5w * (7 + w)) = 0
((28 + 4w) + 5w * (7 + w)) = 0
(28 + 4w + (7 * 5w + w * 5w)) = 0
(28 + 4w + (35w + 5w2)) = 0

Combine like terms: 4w + 35w = 39w
(28 + 39w + 5w2) = 0

Solving
28 + 39w + 5w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(7 + w)(4 + 5w) = 0

Subproblem 1

Set the factor '(7 + w)' equal to zero and attempt to solve: Simplifying 7 + w = 0 Solving 7 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + w = 0 + -7 Combine like terms: 7 + -7 = 0 0 + w = 0 + -7 w = 0 + -7 Combine like terms: 0 + -7 = -7 w = -7 Simplifying w = -7

Subproblem 2

Set the factor '(4 + 5w)' equal to zero and attempt to solve: Simplifying 4 + 5w = 0 Solving 4 + 5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5w = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5w = 0 + -4 5w = 0 + -4 Combine like terms: 0 + -4 = -4 5w = -4 Divide each side by '5'. w = -0.8 Simplifying w = -0.8

Solution

w = {-7, -0.8}

See similar equations:

| 3x^7+fs=5 | | 6+9=12 | | 5x+9845739457=2 | | 6x-19=x+10 | | 13s-31=9 | | 4x^3-2/x^4 | | X+4x-8.2=16-3x | | y=0.55x+1.75 | | (5w-1)(w+3)=0 | | Dr/t | | x+(7+x)=170 | | (1/2)ln9 | | 30*.25= | | X1/2=7 | | X(m+n)-3(m+n)=0 | | -28=-8x+4 | | .59*180= | | -2=r-2/2 | | ln(x^2-9)-ln(x+3)=2 | | 2b^2=144-b^2 | | 28=21*x | | 2b^2=144-2b^2 | | -x+3y=-25 | | 20-u=7 | | 42p=4-2p+8 | | x-2=14-6x+3 | | 16xf=176 | | 18a^2+46a-24=0 | | 5/2.1/2 | | 16-6a=-5-3a | | 5/2/12 | | (4x-1)(1+4x)= |

Equations solver categories